Analysis of deficit irrigation strategies for corn using crop growth simulation - Stockle, CO; James, LG (Springer, 1989)
Corn yields for full irrigation and 4 different levels of deficit irrigation were simulated using a model developed by Stockle and Campbell (1985). Different irrigation levels were obtained by holding the application depth constant and allowing the irrigation interval to vary from 1 to 5 days. Silt loam and loamy sand soils, two root depths, two water contents at planting time, total pumping heads ranging from 0 to 800 m, four ratios of energy cost to commodity price and climatic data for the 1974 growing season at Davis, California were examined. The different variable combinations resulted in a wide range of crop water deficit and yield. Results indicated that, for given combinations, slight deficit (ratios of actual to potential transpiration larger than 0.89) provided higher net benefit than full irrigation. Larger deficits were never advantageous across the diverse range of conditions examined, indicating that potential benefits are associated with only a narrow range of irrigation deficits. This result illustrates the risk involved when deficit irrigation is practiced. Large soil water holding capacity, high soil water contents at planting and deep root exploration were found important for successful implementation of deficit irrigation. Total pumping head and the ratio of energy cost to commodity price were important factors in determining the feasibility of deficit irrigation for the conditions examined. It was also found that the level of irrigation which maximized net benefits tended to be lower for situations where the quantity of water available for irrigation was fixed and the amount of land which could be irrigated was unlimited than when there was sufficient water to fully irrigate the entire farm. Situations where deficit irrigation is a more effective way of reducing energy cost than reducing system operating pressure were ob served.